The strength of weight‐bearing bones is similar in amenorrheic and eumenorrheic elite long‐distance runners. (15th February 2018) - Piasecki, J.; Ireland, A.; Piasecki, M.; Cameron, J.; McPhee, J. S.; Degens, H.
Abstract : Regular intense endurance exercise can lead to amenorrhea with possible adverse consequences for bone health. We compared whole body and regional bone strength and skeletal muscle characteristics between amenorrheic (AA: n = 14) and eumenorrheic (EA: n = 15) elite adult female long‐distance runners and nonathletic controls (C: n = 15). Participants completed 3‐day food diaries, dual‐energy X‐ray absorptiometry (DXA), magnetic resonance imaging (MRI), peripheral quantitative computed tomography (pQCT), and isometric maximal voluntary knee extension contraction (MVC). Both athlete groups had a higher caloric intake than controls, with no significant difference between athlete groups. DXA revealed lower bone mineral density (BMD) at the trunk, rib, pelvis, and lumbar spine in the AA than EA and C. pQCT showed greater bone size in the radius and tibia in EA and AA than C. The radius and tibia of AA had a larger endocortical circumference than C. Tibia bone mass and moments of inertia (Ix and Iy) were greater in AA and EA than C, whereas in the radius, only the proximal Iy was larger in EA than C. Knee extensor MVC did not differ significantly between groups. Amenorrheic adult female elite long‐distance runners had lower BMD in the trunk, lumbar spine, ribs, and pelvis than eumenorrheic athletes and controls. The radius and tibia bone size and strength indicators were similar in amenorrheic and eumenorrheic athletes, suggesting that long bones of the limbs differ in their response to amenorrhea from bones in the trunk.